Gluteal muscle function and size in swimmers - Semciw, A. I.; Green, R. A.; Pizzari, T. (Journal of Science and Medicine in Sport, 2016)
Objectives: To compare the gluteus medius and minimus segments size and activity in swimmers versus non-swimmers. Design: Case matched-control cross-sectional study. Methods: The three segments of gluteus medius (anterior, middle and posterior) and two segments of gluteus minimus (anterior and posterior) were evaluated using electromyography and magnetic resonance imaging in 15 swimmers (7 elite and 8 non-elite) and 15 gender- and aged-matched controls. For each muscle segment, values were obtained for peak amplitude, average amplitude, and time to peak from each phase of the gait cycle (0-20%, 20-60%, and total stance). Results: The pattern of anterior gluteus minimus EMG activity in swimmers demonstrated additional activity early in the gait cycle when compared with controls. The segmental differences between anterior and posterior gluteus minimus during gait identified in the control group were not present in the swimmers. Overall, there were no significant differences in the gluteus medius EMG characteristics between groups and muscle size was not significantly different between groups for any of the hip abductor muscles. Conclusions: The preliminary evidence of non-segmental differences within the gluteus minimus of swimmers (as opposed to non-swimmers) might implicate reduced-gravity environments in contributing to subsequent changes in deep stabiliser muscles. Such changes might predispose the athlete to a greater risk of lower limb injury during weight bearing activities.